Analysis of geographic knowledge about the American continent of new students at the History Course of the University of Córdoba, Spain (PerCursos, 2025)
The main objective of the paper is to analyze the degree of geographic knowledge that new students of the History Degree of the University of Córdoba (Spain) have about America. A total of 45 subjects have participated in the study who have answered a questionnaire prepared in order to collect information about their knowledge about the American continent. The results show that the degree of knowledge of the students is not very high and that there are contrasts between the different branches that make up Geography. It is worth highlighting the suitability of carrying out similar studies for other territories in order to find out what the students know about them
Keywords: American; teaching; learning; geography; university student